Comparison of the Morse Cone Connection with the Internal Hexagon and External Hexagon Connections Based on Microleakage - Review - Bittencourt, Ana Beatriz Bueno Carlini [UNESP] (2021)
The gap formed at the abutment-implant interface brings about a bacterial colonization. In addition, a bacterial reservoir can be established within the implant. The build-up of microorganisms around the implant can cause soft tissue infections and bone loss around the implant, which can lead to implant failure. Our literature review aimed to evaluate the infiltration at the implant-abutment interface, comparing the Morse cone connection with the external hexagon and internal hexagon connections. A literature search using the PubMed database was performed on March 24, 2021. The search terms were combinations of Morse cone or Morse taper with each of the following terms (individually): microleakage, leakage, infiltration, and penetration. The inclusion criterion was in vitro studies comparing the Morse cone with the external hexagon and/or internal hexagon, based on infiltration at the implant-abutment interface. The exclusion criterion was the evaluation of microleakage at the implant-abutment interface after applying a sealant over this region. The search was expanded as needed. There was no limit on the year of publication, and only articles written in English were included. In addition, references cited in included articles were also included in this review when they were appropriate. This literature review concluded that, in most cases, the microleakage in the Morse cone connection was lower when compared with the external hexagon and internal hexagon connections.